Reinforced concrete structural reliability - El-Reedy, Mohamed A. (CRC Press, 2013)
Structural engineers must focus on a structure's continued safety throughout its service life. Reinforced Concrete Structural Reliability covers the methods that enable engineers to keep structures reliable during all project phases, and presents a practical exploration of up-to-date techniques for predicting the lifetime of a structure. The book also helps readers understand where the safety factors used come from and addresses the problems that arise from deviation from these factors. It also examines the question of what code is best to follow for a specific project: the American code, the.